The Role and Contribution of the British Administration and the Capitalist in the North Borneo Fishing Industry, 1945-1963 - Ali, Ismail (SOSIOHUMANIKA, 2009)
ABSTRACT: Although the aims and roles played by the Crown Colony administration and the Chinese, Japanese and Hong Kong capitalists were different, the combination between the government and the capitalists was successful in redeveloping the North Borneo fishing industry after World War II (1939-1945). As for the capitalists, the Crown Colony administrationâs policies â which avoided direct intervention in the fishing industry, specifically in the fishing and selling activities â had given them ample opportunity to gain a huge amount of profit. Therefore, it can be said that the roles and contributions of the British government, as well as the local and foreign capitalists, were only successful in redeveloping the North Borneo fishing industry after World War II, but did not succeed in improving the lives of the local fishermen. The conflict of interest, which rose from the question of economical and social obligations, resulted in the British administration acting as merely a âpurveyorâ of technology and fishing equipment for the fishermen and not contributing much towards helping the fishermen to find the means of getting these items. This allowed the local and foreign capitalists to fill the gap and to control the fishing industry by bringing in better fishing technology, exploiting the local fishermen by providing a credit system for the procurement of the fishing equipment and eventually transforming the local fishermen as merely a source of manpower.Key words: Crown Colony administration, the capitalists, North Borneo fishing industry, and transforming the local fishermen.About the Author: Assoc. Prof. Dr. Ismail Ali is a Senior Lecturer at the Programme of History, School of Social Sciences UMS (Malaysia University of Sabah). For academic purposes, he can be reached at: ismailrc@ums.edu.myHow to cite this article? Ali, Ismail. (2009). âThe Role and Contribution of the British Administration and the Capitalist in the North Borneo Fishing Industry, 1945-1963â in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.2 [November], pp.155-164. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 19, 2009); Revised (October 21, 2009); and Published (November 20, 2009).